Intelligent tutoring effects on induced emotions and cognitive load of learning-disabled learners - Dutt, Sarthika; Ahuja, Neelu Jyothi (Disability and Rehabilitation: Assistive Technology, 2024)
This study addresses the learning requirements of learners with learning difficulties by monitoring their learning experience in an Intelligent Tutoring System. Intelligent Tutoring Systems were developed to enrich the teaching-learning process. In the present work, the interface is designed and developed utilizing the potential of Artificial Intelligence to meet their individual needs. Designing an online learning platform for a learners with learning difficulties requires consideration of their learning problems and preferences. The interface was developed focusing on all the requirements of the LD learners. The objective of the present study is to monitor the learning experience in the form of induced emotions and cognitive load of the learners to determine the impact of learning. 83 learners were observed during various stage of learning. The results obtained through the Support Vector machine (SVM) classification technique showed the positive attitude towards intelligent tutoring. The analysis revealed that a total of 0.23% of learners were positively induced. Their learning experience was positive and effective. The cognition load on learners was minimum with single-mode instruction and least disturbed. The system was improved based on preference feedback on design features. This helps in improving content design and creating device independent and responsive visual design. The fatigue effect analysis on cognitive load implied that multiple modes of instruction increased drowsiness. Single mode of instruction have a positive impact on the learning process and it reduces the cognitive load of the learners.Implications for RehabilitationThe user interface designed and developed for learners with Dyslexia, Dysgraphia and Dyscalculia has learning disabled-friendly features. These can be used to create a device-independent and responsive design.Learning experience is monitored along with the impact on cognitive load of the learners.The research helps in understanding the stimulation and response of learners with learning disability for different learning conditions.Most existing learning systems are limited to non-learning-disabled learners. The ITS developed during research presents a Universal learning design helpful for all learners with and without learning disability. The user interface designed and developed for learners with Dyslexia, Dysgraphia and Dyscalculia has learning disabled-friendly features. These can be used to create a device-independent and responsive design. Learning experience is monitored along with the impact on cognitive load of the learners. The research helps in understanding the stimulation and response of learners with learning disability for different learning conditions. Most existing learning systems are limited to non-learning-disabled learners. The ITS developed during research presents a Universal learning design helpful for all learners with and without learning disability.
Publisher: Taylor & Francis _eprint: https://doi.org/10.1080/17483107.2024.2357685 <AI Smry>: The interface is designed and developed utilizing the potential of Artificial Intelligence to meet the needs of learners with learning difficulties utilizing a Universal learning design helpful for all learners with and without learning disability.
Keywords: Educational Area: Inclusion; Educational Area: Student Learning; Evidence: Self-reported Student Behaviour/ Attitude; Location: Asia; Research Design: Interview/ focus group; Research Method: Qualitative; Source: Closed Source